Yesterday, Today, and Tomorrow: Obama, In the Heights, and Movies About People From the Islands. (2nd October 2021) - Beck, Bernard
Abstract : The movies can be part of sudden and thorough revelations of attitudes toward current events. The ambiguities of our history can be seen in the swings of public sentimentality. In the movies, these swings are highlighted. Our deepest sentiments can be unexpectedly unstable. What we find in the movies can emphasize these discontinuities. West Side Story, Hamilton, In the Heights, and Obama: In Pursuit of a More Perfect Union display some interesting differences in movies about similar themes. The endurance of underlying unresolved issues of immigration and conflict are reflected in the history of popular culture. The deepest of all these issues is our unresolved problem of race.